Las herramientas tecnológicas y su incidencia en el desarrollo de la lecto- escritura en las niñas de segundo año de la Escuela Elvira Ortega del cantón Latacunga en el periodo lectivo 2013-2014 - Tipán Guanoluisa, Pablo Agustín (2015)
This research was focused in the Elvira Ortega school, and focuses on implementing technological tools for teaching reading and writing skills as an impact on the teaching-learning process in children of the institution, as well as technology influences to develop cognitive, procedural and attitudinal part of the students, especially if students are in the ability to manipulate these tools that are consistent with the of knowledge age that they should receive from their teachers; also was based on knowing whether teachers are actually trained to impart knowledge in the use of educational software in the area of language and literature, it should be emphasized that the use of technological tools to impart any knowledge is fundamental and essential to improve output profile from students and have no deficiencies updated knowledge learning standards requires us, as well as strengthening the three types of knowledge that should be imparted in our students to be able to solve problems of everyday life that they present throughout their school life and diary life.